Latent profiles of children’s autonomic nervous system reactivity early in life predict later externalizing problems - Roubinov, Danielle (Dev Psychobiol, 2020)
Prior researchers have observed relations between children’s autonomic nervous system reactivity and externalizing behavior problems, but rarely considers the role of developmentally-regulated changes in children’s stress response systems. Using growth mixture modeling, the present study derived profiles of parasympathetic nervous system reactivity (as indicated by respiratory sinus arrhythmia (RSA)) and sympathetic nervous system reactivity (as indicated by pre-ejection period (PEP)) from low income, primarily Mexican American children measured repeatedly from infancy through age 5 (N = 383) and investigated whether profiles were associated with externalizing problems at age 7. Analyses identified two profiles of RSA reactivity (reactive-decreasing and U-shaped reactivity) and three profiles of PEP reactivity (blunted/anticipatory reactivity, reactive-decreasing, non-reactive increasing). Compared to children with an RSA profile of reactive-decreasing, those with an RSA profile of U-shaped reactivity had marginally higher externalizing problems, however this difference was not statistically significant. Children who demonstrated a profile of blunted/anticipatory PEP reactivity had significantly higher externalizing problems compared to those with a profile of non-reactive increasing, likely related to the predominantly male composition of the former profile and predominantly female composition of the latter profile. Findings contribute to our understanding of developmental trajectories of ANS reactivity and highlight the utility of a longitudinal framework for understanding the effects of physiological risk factors on later behavior problems.